Mechanism and Persistence Dormancy of Ground Cherry Seeds (Physalis peruviana L.) at Different Maturity Stages - Pradana, Adhitya Vishnu; R. Palupi, Endah; Qadir, Abdul; Widajati, Eny (Journal of Tropical Crop Science, 2022)
Ground cherry (Physalis peruviana) seeds have a period of dormancy after ripening. A study was conducted to understand the mechanism of dormancy, the duration of after ripening persistence, and to determine the effective methods to break dormancy. The study was conducted in an experimental field at Ciwidey, West Java, Indonesia, and the Seed Testing Laboratory, Faculty of Agriculture, Department of Agronomy and Horticulture, IPB University, in February to November 2020. The first study examined the effects of the storage temperatures, i.e. 20 ±2 oC and 25 ± 2oC, and the seed maturity stages, i.e. 49 days after anthesis (DAA), 58 DAA and 62 DAA. Several methods to break seed dormancy were tested, i.e. soaking seeds for 24 hours in distilled water, in 0.5% or 1% KNO3 and, 50 ppm GA3. The results showed that the seed dormancy was broken at 7 weeks after treatment, indicated by seed germination of >80%. The ABA levels of the seeds declined from week 0 to week 11, and the seed ABA and GA reached a balance from week 7 to week 11. Seeds treated with KNO3 or distilled water break dormancy after 8 weeks. The most effective treatment to break seed dormancy is the use of exogenous hormone GA3 at 50 ppm, with seed germination of >80% at week 5.